Testament świątobliwej Ofki Piastówny OP, przeoryszy raciborskich dominikanek z 1358 roku - Stefaniak, Piotr (Archiwa, Biblioteki i Muzea Kościelne, 2017)
On 8 December 1258, an almost sixty-year-old prioress of the Racibórz Dominican Nuns, Ofka Piastówna, made a will before a notary public, Piotr Gotfridi, a presbyter of Wrocław. It is one of the two known legal documents of this type from the Middle Ages, which were produced by a nun coming from a noble family living on Polish soil. On this occasion the Dominican monastery in Racibórz hosted the notables from the local duke's court, including Mikołaj II Przemyślida, representatives of the knighthood, the burghers and the authorities of the Polish Dominican Province. In her will, Ofka secured the economic prosperity of the monastery, which was headed by her, and founded by her father, Duke Przemyslaw Piastowicz. The will which was prepared in Latin in two similar versions was held by the Racibórz Dominican Nuns in the archives to the moment of the dissolution of their monastery ordered by Frederick William III on 30 October 1810. Then, together with other documents, it was finally stored in the State Archives in Wrocław, where it was destroyed or stolen at the end of the war in 1945. Now we know this document from the CodexdiplomaticusSilesiae edition.